Extension of Beauveria bassiana the Effectiveness As a Coffee Fruit Borer Pest Control in Ngrayudan Village, Ngawi Regency - Farasifa, Aida Putri; Purwanti, Eny Wahyuning; Gunawan, Gunawan (CV. Komunitas Dunia Peternakan, 2024)
The development of coffee cultivation in Ngrayudan Village, Ngawi Regency has experienced a decline in quality due to the attack of the Coffee Fruit Borer pest. The pest causes damage to the coffee fruit. Based on the results of the identification of the area potential, there is a problem regarding the handling of Coffee Fruit Borer pests that had not been maximized by farmers in Ngrayudan Village. Farmers do not have the knowledge and skills to use biological agents as solutions. This study aims to design extension and behavior changes related to farmers' knowledge, attitudes, and skills. This research was conducted in February - March 2024 using a qualitative approach by using the level III action research method which has four stages in extension activities including planning, action, observation, and reflection. Based on observations and interviews with respondents after counseling showed significant changes in behavior. Supported by quantitative data from the extension evaluation results which showed an increase in knowledge of 34%, while the attitude level showed results of 89% including in the category of responsibility in deciding a matter, and a skill level of 80% including in the level of problem-solving farmers can describe problems to find the best solution. The conclusion of this study shows the existence of effective extension in improving behavior change in Farmer Groups in making biological agents such as Coffee Fruit Borer pest control.